Social justice case studies : interdisciplinary and non-traditional interdisciplinary approaches - Green, Cheryl (Emerald points., 2023)
Social Justice Case Studies: Interdisciplinary and Non-Traditional Interdisciplinary Approaches provides individuals interested in social justice the ability to discuss and engage in interdisciplinary and non-traditional interdisciplinary team processes. Using case studies that address a range of social justice issues, Dr. Cheryl Green explores the roles of interdisciplinary team members and how they can positively or negatively impact clients' outcomes. Chapters discuss approaches to management of complex client cases, as well as ethical dilemmas, facilitation of family meetings, discharge planning, cultural consideration, and burnout prevention. Dr. Green considers case studies involving intimate partner violence between a same-sex couple, a college student's experience of Espiritismo, counselling and support for women facing unplanned pregnancies, support for a transgender client undergoing familial conflict, and the recognition of "fright" in a male of Caribbean descent experiencing depression and anxiety. Important, timely, and topical, Social Justice Case Studies: Interdisciplinary and Non-Traditional Interdisciplinary Approaches is an accessible read for those interested in challenging the issues that impact social justice across a variety of settings.